Evaluación de la prevalencia de caries y enfermedad periodontal en los pacientes con tratamiento de ortodoncia fija en la Facultad de Odontología, primer semestre de 1995 - Agudelo-G., Walter; Cano-A., Alonso; Cuartas-E., María Elena (Revista Facultad de Odontología Universidad de Antioquia, 2016)
Until the present moment there have not been studies to evaluate the dental and periodontal conditions of the patients in orthodontic treatment of the Faculty of Dentistry from the University of Antioquia. The objetive of this study was to determinat the oral hygiene. (bacterian plaque index), dental health (COP index and incipient decay presence), and the periodontal conditions, (existence of gingival retraccions and gingival index). Furthermore the habits of oral hygiene, feeding habits, the time with the aparatology and its relation with each of the index were establized. The gingival index, plaque index and COP were also related with every variable: age, sex, educational level of instruction in oral hygiene. A total of 71 patients 828 men, 43 women) in ages between 10 and 24 years that had only orthodontic fix aparatology were evaluated. It was found that the plaque index were always bigger in the group of 10 to 14 year, and that the gingival index, and COP were lightly bigger in men than in women and that the number of times that oral hygiene instruction was given, has positive influence in the COP, gingival and plaque indexes. It was found also that the dental floss is used by a very low percentage of patients and that the time with the orthodontic aparatology, can become a risk for the development of the tooth decay, because the actual COPs, was stadisticaly higher that the initial COPs.